Exploring the Use of Digital Communication Channels as a Means of Employee Communication and Internal Brand Strategy Within South African Corporate Companies - Johnson, Michaela (Centre for Film and Media Studies, 2024)
This research paper aims to understand how the digital acceleration, engendered by the COVID-19 pandemic, affected employee communication in the remote workplace. For brevity, focus is maintained on South African companies only. Particular emphasis is placed on digital communication channels' use to engage employees. With these two design principles, this study develops to sparse literature of South African companies' use of digital communication. Six medium to large companies that represent the key industries of South Africa have been sampled; mining, logistics, tourism, insurance and finance. The companies interviewed are the top South African businesses within in their respective industries. These companies include insurance companies Sanlam and Old Mutual, gold mining company Sibanye Stillwater, logistics company Imperial Logistics, tourism company Cape Town Tourism, and retail banking company Capitec Bank. The representatives selected in each company were based on the role they played in the implementation and operation of the digital communication channel within the organization. These roles ranged from heads of brand, heads of group strategy, and heads of communication. Qualitative interviews were preferred for data gathering and a grounded theory and thematic analysis approaches were used to analyse the data. The full sample of six companies were found to blend company-owned mobile communication and third party-owned software platforms to communicate in online spaces. Research additionally found remote communication strengthening organizational identity in most cases. This was arguably due to synchronous communication emphasizing employee wellness. Resistance to adoption of remote communication channels was offset with relevant training. Further study of this emergence of resistance led to identifying employees need to negotiate work- and home-identity in remote work environments. Studying this work/ home balance further led to a study of employee comfort. Findings in this area point to a proportional relationship between employee comfort and clear, direct and personalised communication. As a consequence of these findings, focus was then shifted to the nature of personalisation in internal branding, which again adds to a limited literature currently available. These shifting areas of focus are used to puzzle out how South African companies are attempting digital transformation. All of which builds to the conclusion that while South African companies might currently prefer enhancing their numerous platforms, conversion to a single protocol is likely, given these companies' openness to digital transformation.